Portal społecznościowy Facebook jako narzędzie realizacji celów edukacji antydyskryminacyjnej - Smoter, Katarzyna (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2014)
Countering social exclusion is becoming a import_ant social issue. Those kinds of activities are developed in the field of anti-discrimination education, (where one of the most meaningful aspects is preventing hate speech). Such activities are undertaken in campaigns and projects, for example: “Bez nienawiści,” “Hejtstop,” “Mowa miłości,” which are promoted on the social network Facebook. They are examples of good practices that should be disseminated and continued, also in the context of formal education.